The THE APPLICATION OF TEACHER ETHICAL VALUES ACCORDING TO IMAM DZAHABI IN MA AL-IRSYAD TENGARAN AND MATIQ AS-SURKATI SALATIGA: PENERAPAN NILAI-NILAI ETIKA GURU MENURUT IMAM DZAHABI DI MA AL-IRSYAD TENGARAN DAN MATIQ AS-SURKATI SALATIGA - Mutaqin, Zaenal; Rifqi Aulia Erlangga (Al-Ihda' : Jurnal Pendidikan dan Pemikiran, 2024)
Among the descriptions of the problems found by researchers is the condition of some teacher ethics that are not in accordance with the goals of Islamic education itself. There are also teachers who do not care about the mistakes of the students they see. In addition, there are still many student violations that are suspected to be the result of the influence of bad teacher ethics. So this study aims to remind good teacher ethics to the ranks of teachers in the two madrasas. This study uses a qualitative descriptive research method. The researcher sees that this method is suitable for this research because the purpose of this research is to describe and explain the ethical values contained in the book siyaar a'laamin nubala by Imam Dzahabi. The results achieved include showing that the teacher always shows a sincere attitude towards the task of teaching students in their work. In general, the ethics of teachers in the two madrasas are in accordance with what was described by Imam Dzahabi in his book Siyaar Alamin Nubala. Meanwhile, teachers should not only improve their quality in terms of intelligence about the material being taught. But teachers also need to pay attention to ethics when in the school environment. Because the attitude and behavior of the teacher has more influence on the quality of their students than the material obtained while in class.